A framework for the safe use of bamboo scaffolding in the Nigerian construction industry. (July 2022) - Sanni-Anibire, Muizz O.; Abiodun Salami, Babatunde; Muili, Nimot
Highlights: The study proposed a framework with six process groups and thirty-five subprocesses for the safe use of bamboo scaffolds. The subprocesses in the framework entailed a set of guidelines covering the life cycle of bamboo scaffolding. The validity of the framework for adoption in the Nigerian construction industry was investigated. Developing countries with abundant sources of bamboo could also adopt the proposed framework. Abstract: The construction industry is one of the most hazardous industries globally. Falls from height due to scaffolding accidents have consistently been ranked as one of the most prevalent accidents in the industry. Although safety programs to mitigate these hazards have been implemented in many developed countries, this is not the case in developing countries such as Nigeria. Previous research studies suggest the lack of guidelines, regulations, and awareness in these countries as the root cause of accidents. Bamboo scaffolds are a common form of access for work at height in Nigeria because of their wide availability, affordability, material strength, and environmental sustainability. However, guidelines for the safe use of this equipment are lacking. This study developed a framework conveyed through a set of guidelines for the safe use of bamboo scaffolds in Nigeria. The guidelines were gathered under 35 subprocesses, which were presented in six process groups: planning, design, erection, operation, inspection and maintenance, and dismantling. The framework was further validated by experts in the construction industry in Nigeria. This study has implications for stakeholders in the construction industry in Nigeria, as well as other similar construction climes in developing countries.